Implementation of HR management functions: A quality-analysis - Wahyudin Noor; Juhji Juhji (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze the practice of Human Resource (HR) management functions in Madrasah Aliyah Negeri (MAN) Yogyakarta III from a quality perspective. The research method used is descriptive qualitative through in-depth interviews, observation, and documentation. Data analysis uses the stages of reduction, presentation, and inference. The results showed that, at MAN Yogyakarta III, the institution's quality is quite influenced by implementing the Human Resource Management (HRM) function, which can be seen in the form of internal and external customer satisfaction. For internal customers, customer satisfaction can be seen from the increase in psychological development, such as opportunities for personnel to continue to learn and develop abilities, assist personnel in developing their talents and creativity as well as efforts to create an atmosphere and culture that can make personnel feel satisfied and comfortable. As for external customers, satisfaction increases physical and psychological development, such as achievement scholarship programs, coaching, parallel achievements, a conducive learning atmosphere, family relationships between teachers and students, good learning services, capacity building, and creativity.